Proses pembelajaran arsitek Belanda terhadap Hindia Belanda - Johannes Adiyanto (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This research concentrates on the architectural process of Dutch architects in the Dutch East Indies, specifically Maclaine Pont, Thomas Karsten, and Wolff Schoemaker. The issue addressed by these three people is how they learned, particularly their reaction to the conditions and wealth of buildings in the Dutch East Indies, and what drove each of their architectures. This study employs a synchronic-diachronic analytic strategy as well as a historical interpretation strategy based on contextual evidence categories. It runs from 1900 to 1940. According to the study's findings, all three encounters through the same learning process, which includes the introduction phase, the exploration phase, and the architectural attitude phase. The architectural perspective was expressed at Maclaine Pont through the design of a tent structure system based on studies of Javanese pavilion roofs, whereas Karsten and Schoemaker referenced modern architecture. Karsten was fascinated by people's daily lives, whereas Schoemaker thought Frank Lloyd Wright's style was the most recent at the time.